Effectiveness of Personnel Recruitment in the Office of the Permanent Secretary for Public Health in Response to the Epidemic of Coronavirus 2019 in Thailand - พรชัยสุขศิริ อุจนีย์; สำเภา ฉวีวรรณ; ประโยชน์ วิไลวรรณ; จันทร์อาภรณ์ ธนินทร์พัทรา (Journal of Health Science of Thailand, 2021)
The Cabinet Resolution on 15 April 2020 approved the allocation for the new positions of civil servants in the Ministry of Public Health (MOPH) to address the emergence of coronavirus 2019 epidemic. It was a special case of the recruitment and appointment for 24 classifications, 38,105 positions which had to be finished within one year, and it was necessary to manipulate of procedures in order to fulfil the time limitation. This study was conducted to assess the effectiveness and process for the recruitment of 34,914 positions for the Office of the Permanent Secretary, Ministry of Public Health. Data were collected through the study of the official government records papers such as the Cabinet Resolutions, the Parliament Acts, as well as participatory observations and focus group discussions among relevant officials. The results of the study showed that the recruitmentr and appointment process was highly effective as 94.7 percent of the positions were filled. The key success factors included the use of a tool, the Human Resource Office of the Permanent Secretary’s System (HROPS) that provided information support to the decisions, to plan, to verify and to solve the concurrent problems. Another important factor was the decentralization of recruitment authority to the provincial public health officer to manage the official procedure at the provincial level. The findings of this study suggested that policy makers should conduct and support the improvement of the HROPS to increase efficiency, accuracy, completeness, and to be readily accessible. In addition, the Human Resource Division of MOPH should review the specifications for the personnel positions to be in line with those of the Office of the Civil Service Commision in order to efficiently and effectively improve the recruitment and appointment procedure both in the ordinary situation and the special emerging events in the future.